Recent progress of effect of crystal structure on luminescence properties of Ce3+–Eu2+ Co-doped phosphors. Issue 42 (2nd August 2021) - Zheng, Mingjie; Wang, Zhijun; Wang, Xuejiao; Cui, Jia; Yao, Yao; Zhang, Mengya; Yang, Zhibin; Cao, Lingwei; Li, Panlai
Abstract : Effect of crystal structure on luminescence properties of Ce 3+ –Eu 2+ co-doped phosphors. Abstract : Currently, the mechanism of Ce 3+ –Eu 2+ ET is frequently used to obtain color adjustable or white phosphors. Correspondingly, the ET efficiency from Ce 3+ to Eu 2+ becomes an important indication of the luminescent properties of phosphors. However, the ET efficiency calculated using the formula does not always match the emission spectra; the transmission efficiency of Ce 3+ is high, but the emission efficiency of Eu 2+ is low, depending on our investigation results. In addition to this problem, here we mainly review, on the basis of substantial examples, how to boost the actual ET efficiency of Ce 3+ -to-Eu 2+ and thus to improve the luminescent properties of phosphors through the rational design of layered crystal structure and the way of selective occupation of activator ions. Moreover, the possible physical mechanisms are proposed.